2020
DOI: 10.1016/j.ajpath.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The Pathobiology of Skin Aging

Abstract: Defining a disease is not an easy task, as it encompasses a variety of factors that include historical perspectives, societal and cultural health expectations, diagnostic sensitivities and thresholds, and socioeconomic issues. Osteoporosis, considered to be a potentially integral component of a long life, became a disease in 1994 when it was converted from Supported by the LEO Foundation grant LF-OC-19-000256 (G.F.M.) and National Cancer Institute (NCI) HTAN Initiative grant 1U2CCA233262-01 (G.F.M.).Disclosure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 115 publications
1
70
0
4
Order By: Relevance
“…The amount of HA and pro-collagen originally contained in BM and FM showed that HA and pro-collagen had higher BM than FM. Skin aging is the result of the inherent chronological aging process superimposed by environmental factors, principally exposed to ultraviolet (UV) radiation [ 3 , 12 ]. These results show that, when tested in UV-B-promoted fibroblast cells, CCD-986SK, the BM produced more HA and pro-collagen than FM and positive controls, which demonstrated to be more effective in anti-wrinkle and skin regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of HA and pro-collagen originally contained in BM and FM showed that HA and pro-collagen had higher BM than FM. Skin aging is the result of the inherent chronological aging process superimposed by environmental factors, principally exposed to ultraviolet (UV) radiation [ 3 , 12 ]. These results show that, when tested in UV-B-promoted fibroblast cells, CCD-986SK, the BM produced more HA and pro-collagen than FM and positive controls, which demonstrated to be more effective in anti-wrinkle and skin regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, stem cell dysfunction and natural wastage appear to be key drivers, and both genetic and epigenetic factors are involved in a complex interaction that over time results in the decline of our main protective interface with the external environment. Past and current understanding of the cellular and molecular intricacies of skin aging provides a foundation for future approaches designed to revert the aging phenotype [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-aging strategies target diverse mechanisms involved in skin aging, such as oxidative stress, mitochondrial dysfunction, cellular senescence, and epigenetic changes [ 1 , 31 , 32 , 33 , 34 ]. For example, melatonin and its metabolites, non-calcemic secosteroids, lumisterol derivatives, polyphenols, and vitamins represent promising anti-aging agents [ 1 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their deficiency acutely removes the self-perpetuating reservoir necessary to maintain epidermal integrity for protection against infection and fluid and electrolyte depletion. During the ubiquitous aging process, chronic, non-immune impairment of skin stem cell number and/or function results in epidermal atrophy, potentially impacting on the numerous protective roles of the epidermal layer [ 19 ]. While multiple mechanisms for stem cell aging and resultant dysfunction have been advanced [ 20 ], Fuchs et al [ 21 ] have recently emphasized follicular stem cells as a model in which transcriptional changes, primarily in extracellular matrix genes accompanied by structural anomalies in the immediate stem cell microenvironment, typify the aging process.…”
Section: Stem Cells In Tissue Health and Agingmentioning
confidence: 99%